2014
DOI: 10.1371/journal.pone.0102094
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Diversification in the Evolution of Coral Reef Fishes

Abstract: The disparity in species richness among evolutionary lineages is one of the oldest and most intriguing issues in evolutionary biology. Although geographical factors have been traditionally thought to promote speciation, recent studies have underscored the importance of ecological interactions as one of the main drivers of diversification. Here, we test if differences in species richness of closely related lineages match predictions based on the concept of density-dependent diversification. As radiation progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 81 publications
(123 reference statements)
14
73
1
Order By: Relevance
“…1), and mirrors the relatively low rates of diversification in a wide range of reef fish taxa (e.g. Alfaro et al, 2009;Cowman & Bellwood, 2013a,b;Lobato et al, 2014). This stasis in early Cenozoic reefs is also reflected in their biogeography.…”
Section: Three Major Phases In the Evolution Of Fishes And Coralmentioning
confidence: 81%
See 3 more Smart Citations
“…1), and mirrors the relatively low rates of diversification in a wide range of reef fish taxa (e.g. Alfaro et al, 2009;Cowman & Bellwood, 2013a,b;Lobato et al, 2014). This stasis in early Cenozoic reefs is also reflected in their biogeography.…”
Section: Three Major Phases In the Evolution Of Fishes And Coralmentioning
confidence: 81%
“…Recent data on genera from Allen & Robertson (1994) and Randall, Allen & Steene (1997). (Floeter et al, 2008;Cowman & Bellwood, 2011), or inferred trophic ecology (Cowman, Bellwood & van Herwerden, 2009;Bellwood et al, 2014aBellwood et al, ,b, 2015aLobato et al, 2014). These changes were summarized for reef fishes in Bellwood et al (2015b) where six phases were identified.…”
Section: Three Major Phases In the Evolution Of Fishes And Coralmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have addressed aspects of functional diversity that are important to reef conservation, encompassing functional insurance, redundancy, and ecosystem services (Micheli et al., ; Mouillot et al., ; Parravicini et al., ). In parallel, phylogenetic studies have examined the evolutionary patterns of a variety of traits in reef fish lineages, aligning their findings to key historical and biogeographical events and evolutionary processes that have shaped reef fish functional diversity (Alfaro et al., ; Erisman, Craig & Hastings, ; Bellwood et al., ; Price et al., ; Frédérich et al., ; Lobato et al., ). Community phylogenetics combines ecology with phylogeny to offer a framework to examine the functional history of an assemblage, but also to address how assemblage structure and function are shaped by evolutionary processes.…”
Section: Functional Evolution Of Reef Fish Assemblagesmentioning
confidence: 99%